Epidemiological and clinical characteristics of 214 families with COVID-19 in Wuhan, China. (April 2021) - Yi, Bo; Fen, Gaoke; Cao, Dedong; Cai, Yuli; Qian, Li; Li, Wei; Wen, Zhongyuan; Sun, Xuan
Highlights: A total of 214 families with 689 members were enrolled in this retrospective study. The attack rate of household COVID-19 transmission was 42.9%, and the median serial interval distribution was 5 days. The case fatality rate was recorded at 8.7% in index patients and 1.7% in cases from non-familial clusters. Abstract: Objective: To investigate the epidemiological dynamics, transmission patterns, and the clinical outcomes of Coronavirus disease 2019 (COVID-19) in familial cluster patients in Wuhan, China. Methods: Between January 22, 2020, and February 4, 2020, we enrolled 214 families for this retrospective study. The COVID-19 cases were diagnosed using real-time reverse-transcriptase polymerase chain reaction (RT-PCR). The number of COVID-19 subjects in a family, their relationship with index patients, the key time-to-event, exposure history, and the clinical outcomes were obtained through telephone calls. Results: Overall, 96 families (44.9%) met the criteria of a familial cluster, which is at least one confirmed case in addition to the index patient in the same household. The secondary attack rate was 42.9%, and nearly 95% of index patients transmitted the infection to ≤2 other family members. High transmission pattern was noted between couples (51.0%) and among multi-generations (27.1%). The median serial interval distribution in familial clusters was 5 days (95% CI, 4 to 6). The case fatality rate was 8.7% in index patients and 1.7% in non-familial clusters patients ( p = 0.023). Conclusions: There is a related higher attack rate and worse clinical outcomes in COVID-19 family clusters.